Sea cucumbers can enhance coral growth and photophysiological performance under field conditions - Cody S. Clements; Mark E. Hay (Coral Reefs, 2026)
Detritivorous sea cucumbers are important processors of reef sediments and have been hypothesized to enhance coral growth by altering local nutrient availability and seawater chemistry, but whether these effects translate into improved coral performance remains untested. We conducted two analogous field experiments in Mo’orea, French Polynesia, to test whether the sea cucumber Holothuria atra enhances coral growth or photosynthetic efficiency. In the first experiment, we enclosed Acropora pulchra with zero versus two sea cucumbers per 0.25 m 2 , approximating natural densities at our site, and found no detectable effect of sea cucumber presence on growth. In 2025, using densities of four per 0.25 m 2 and enclosing three coral species, A. pulchra growth was 41% greater and Pocillopora verrucosa growth was 17% greater in cages with versus without sea cucumbers. The photosynthetic efficiency of Pocillopora verrucosa was also increased, but that of A. pulchra was not. Porites rus showed no significant response for either metric. Thus, sea cucumbers can enhance coral growth and photophysiological performance under field conditions, but these benefits vary across species, response variables, and apparently sea cucumber density. As sea cucumbers have been widely depleted from tropical reefs, identifying the mechanisms and density thresholds governing these effects will be important for understanding the ecological consequences of their loss and their potential role in supporting coral reef stability or recovery.

Historic coral disturbance versus current coral restoration: insights from Palmyra Atoll - Cody S. Clements; Noam T. Altman-Kurosaki; F. Joseph Pollock; Mark E. Hay (Coral Reefs, 2026)
The utility of passive vs. active coral restoration continues to be debated as reefs decline worldwide. Here, we evaluated the efficacy of coral transplantation into the degraded East and Center lagoons of Palmyra Atoll. Corals have failed to recover in these sites over the eight decades since disturbances associated with World War II, despite high coral cover elsewhere around the atoll that could theoretically provide source propagules. We explicitly compared (i) species beginning to recolonize the lagoons with species common elsewhere at Palmyra, (ii) performance between the East and Center lagoons, and (iii) coral growth at sites near vs. far from causeway inlets as a proxy for the benefits of flow. We found that six common coral species were all physiologically capable of growing in the lagoon, but there were: i) large among-species difference in survival, ii) less, but still significant, differences in growth among species, and iii) localized differences in growth and survival across the eight test locations. Many of these differences appeared to be driven by patterns in fish predation on corals. Survival was greatest for Porites and Pavona species, neither of which have substantially colonized the lagoons. Their superior performance relative to Acropora and Pocillopora species that have begun to recolonize the East Lagoon suggests that transplantation of hardier Porites and Pavona species may accelerate recovery. Coral reef restoration efforts often focus on more threatened and fragile corals like Acropora and Pocillopora . Prioritizing the initial planting of hardier corals like Porites and Pavona may help establish foundational reef functions before introducing more fragile species.

Pharmacokinetics and Pharmacodynamics of Nomlabofusp in Non-clinical Studies of Friedreich’s Ataxia - Flavia De Toni; Vanessa Ragaglia; Devin Schecter; Angela S. Miller; Eric Gonzalez; Erik J. Wagner; Xin Xu; R. Mark Payne; Jean-Nicholas Mess; Matthew G. Baile; Adrienne Clements-Egan; Gopi Shankar (The AAPS Journal, 2025)
Nomlabofusp is a cell penetrant peptide-based recombinant fusion protein designed to enter cells and deliver human frataxin into the mitochondria of adults and children with Friedreich’s ataxia. In this article we present non-clinical studies evaluating the pharmacology of nomlabofusp, including in a murine striated muscle tissue frataxin knockout model of Friedreich’s ataxia. We demonstrate that subcutaneous administration of nomlabofusp distributes in a dose-dependent manner to several organs including the dorsal root ganglion, heart, and skeletal muscle, which are known to be predominantly affected in Friedreich’s ataxia, as well as to other tissues, including skin. Plasma nomlabofusp concentrations correlated with levels of human frataxin delivered by nomlabofusp into tissues, and the increases in frataxin were correlated amongst tissues, especially with skin. In the knockout mice, we show that the pharmacokinetics and processing of nomlabofusp were comparable with wild type animals and that treatment with nomlabofusp halts the progression of cardiac dysfunction and significantly increased survival. Together, the findings from these non-clinical studies demonstrate that nomlabofusp exposure increases human frataxin in Friedreich’s ataxia-relevant tissues and provide evidence of pharmacologic effects. Graphical Abstract

Biodiversity of macroalgae does not differentially suppress coral performance: The other side of a biodiversity issue - Cody S. Clements; Zoe A. Pratte; Frank J. Stewart; Mark E. Hay (Ecology, 2024)
Hundreds of studies now document positive relationships between biodiversity and critical ecosystem processes, but as ecological communities worldwide shift toward new species configurations, less is known regarding how the biodiversity of undesirable species will shape the functioning of ecosystems or foundation species. We manipulated macroalgal species richness in experimental field plots to test whether and how the identity and diversity of competing macroalgae affected the growth, survival, and microbiome of a common coral in Mo'orea, French Polynesia. Compared to controls without algal competitors, coral growth was significantly suppressed across three macroalgal monocultures, a polyculture of the same three macroalgae, and plots containing inert seaweed mimics; coral mortality was limited and did not differ significantly among treatments. One macroalga suppressed coral growth significantly less than the other two, but none differed from the inert mimic in terms of coral suppression. The composition, dispersion, and diversity of coral microbiomes in treatments with live macroalgae or inert plastic mimics did not differ from controls experiencing no competition. Microbiome composition differed between two macroalgal monocultures and a monoculture versus plastic mimics, but no other microbiome differences were observed among macroalgal or mimic treatments. Together, these findings suggest that algal diversity does not alter harmful impacts of macroalgae on coral performance, which could be accounted for by physical structure alone in these field experiments. While enhancing biodiversity is a recognized strategy for promoting desirable species, it would be worrisome if biodiversity also enhanced the negative impacts of undesirable species. We documented no such effects in this investigation.

Impacts of climate change on mangrove subsistence fisheries: a global review - Roann P. Alberto; Judith A. Teano; Annie Melinda Paz-Alberto; Mark Anthony B. Tangonan; Hazel Jade E. Villamar; Sarah Clement; David J. S. Montagnes; Andrew P. Morse (Marine Life Science & Technology, 2024)
Climate change will impact coastal ecosystems, threatening subsistence fisheries including those in mangrove forests. Despite their global contributions and roles in nutrition and cultural identity, mangrove subsistence fisheries are poorly studied. Here, we offer a foundation for improving the management of mangrove subsistence fisheries to deal with the impending effects of climate change. This multidisciplinary review—drawing on organismal biology, ecology, fisheries, and social science—focuses on the climate impacts relevant to mangrove ecosystems: heat waves, low-category, and high-category typhoons. First, we provide an overview of the mangroves, their harvestable stocks (fish, crustaceans, molluscs), and the fishers, offering an understanding of how they may be affected by relevant environmental variables; i.e., shifts in temperature, salinity, oxygen, flooding, and sediments. Then, we examine the potential effects of climate change on mangrove stocks and fishers, indicating the scope of impending changes. By combining the above information, we develop a simple model that forecasts the number of “fishing-days” lost by fishers due to climate change over the next decade (between 11 and 21 days will be lost per year per fisher). This indicates which aspects of climate change will have the greatest impacts on stocks and fishers. We found that high-category typhoons had more impacts than heat waves, which in turn had a greater impact than low-category typhoons). Finally, recognising gaps in our knowledge and understanding, we offer recommendations for approaches for future work to improve our predictions.

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Variance of coral anti-pathogen defense in response to transplantation between coral- and macroalgal-dominated reefs - Deanna S. Beatty; Cody S. Clements; Jinu Mathew Valayil; Simone Y. Jarvis; Kim B. Ritchie; Frank J. Stewart; Mark E. Hay (Coral Reefs, 2022)

Did the historic overharvesting of sea cucumbers make coral more susceptible to pathogens? - Natalie Grayson; Cody S. Clements; Alexandra A. Towner; Deanna S. Beatty; Mark E. Hay (Coral Reefs, 2022)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

The association of ultraviolet radiation-B (305 nm), season of diagnosis, and latitude on the survival outcome of prostate cancer in the high UV environment of Australia - Visalini Nair-Shalliker; David P. Smith; Sam Egger; Mark S. Clements; Md. Bayzidur Rahman; Bruce K. Armstrong (Cancer Causes & Control, 2013)

Estimating prevalence of distant metastatic breast cancer: a means of filling a data gap - Mark S. Clements; David M. Roder; Xue Qin Yu; Sam Egger; Dianne L. O’Connell (Cancer Causes & Control, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Identification of the endangered Australian orchid Microtis angusii using an allele-specific PCR assay - Nicola S. Flanagan; Rod Peakall; Mark A. Clements; J. Tupac Otero (Conservation Genetics, 2007)

Conservation of taxonomically difficult species: the case of the Australian orchid, Microtis angusii - Nicola S. Flanagan; Rod Peakall; Mark A. Clements; J. Tupac Otero (Conservation Genetics, 2006)

Modelling of congenital nystagmus waveforms produced by saccadic system abnormalities - David S. Broomhead; Richard A. Clement; Mark R. Muldoon; Jonathan P. Whittle; Columba Scallan; Richard V. Abadi (Biological Cybernetics, 2000)